2011
DOI: 10.1068/p7062
|View full text |Cite
|
Sign up to set email alerts
|

Narcissistic People Cannot Be Moved Easily by Visual Stimulation

Abstract: We examined the relationship between personality and visually induced self-motion perception (latency, duration, and magnitude). A psychological experiment with radially expanding patterns that induced self-motion perception along the fore and aft axis was conducted, followed by personality assessments. We found that all the measures of self-motion perception we examined correlated negatively with the degree of narcissistic traits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Popular topics of research in this area have included the role of stimulus naturalism/realism in illusory vection (e.g., Schulte-Pelkum et al, 2003; Riecke et al, 2005, 2006; Bubka and Bonato, 2010; Riecke and Schulte-Pelkum, 2013), the effect of knowledge about the possibility of actual motion on illusory vection (Lepecq et al, 1995; Palmisano and Chan, 2004; Schulte-Pelkum et al, 2004; Wright et al, 2006; Riecke, 2009), the role of experimental instructions and demands on illusory vection (Palmisano and Chan, 2004; Ogawa and Seno, 2014), the effects of mental imagery on vection (Mast et al, 2001), the effects of stimulus meaning on vection (e.g., figure-ground status and semantic meaning; Seno et al, 2009; Seno and Fukuda, 2011; Ogawa and Seno, 2014) and even the effects of the observer’s own personality characteristics on vection (such as narcissism – Seno et al, 2011d). One intriguing recent study has even reported that vection can be induced solely by cognition (i.e., in the absence of explicit motion – Seno et al, 2012a).…”
Section: Challenge 3: the Need For Objective Indicators Of Vectionmentioning
confidence: 99%
“…Popular topics of research in this area have included the role of stimulus naturalism/realism in illusory vection (e.g., Schulte-Pelkum et al, 2003; Riecke et al, 2005, 2006; Bubka and Bonato, 2010; Riecke and Schulte-Pelkum, 2013), the effect of knowledge about the possibility of actual motion on illusory vection (Lepecq et al, 1995; Palmisano and Chan, 2004; Schulte-Pelkum et al, 2004; Wright et al, 2006; Riecke, 2009), the role of experimental instructions and demands on illusory vection (Palmisano and Chan, 2004; Ogawa and Seno, 2014), the effects of mental imagery on vection (Mast et al, 2001), the effects of stimulus meaning on vection (e.g., figure-ground status and semantic meaning; Seno et al, 2009; Seno and Fukuda, 2011; Ogawa and Seno, 2014) and even the effects of the observer’s own personality characteristics on vection (such as narcissism – Seno et al, 2011d). One intriguing recent study has even reported that vection can be induced solely by cognition (i.e., in the absence of explicit motion – Seno et al, 2012a).…”
Section: Challenge 3: the Need For Objective Indicators Of Vectionmentioning
confidence: 99%
“…Although much is known about how to produce vection in humans with such spatial, dynamic sensory information, less is known about how aspects of the self that might interact with the experience of self-motion as a form of embodied cognition, though there is tantalizing evidence that a relation exists. Seno found a relationship between vection and personality: narcissistic people were less affected by motion, presumably because they are more self-focused than environmentally aware (Seno et al, 2011 ). If one's self is the reference frame through which the world is perceived, then a more narcissistic perspective would give less weight to external stimulation, with a greater bias toward internally generated perceptual states.…”
Section: The Overlap In Social and Spatial Behavior And Its Neurophymentioning
confidence: 99%
“…Con-sidering previous studies, we predicted that vection could be modulated by audience presence. In our previous vection studies, vection was reported in 70% of all stimulus presentation period (Seno et al, 2011a(Seno et al, , 2011b(Seno et al, , 2011c(Seno et al, , 2011d, and was thus the dominant task outcome. We predicted that perception of vection would be facilitated and that the duration of vection would be elongated by audience presence.…”
Section: Introductionmentioning
confidence: 79%
“…Relationships between vection and attention (Seno et al, 2011a), time perception (Seno et al, 20011b), memory (Seno et al, 2013), the effect of alcohol consumption (Seno & Nakamura, in press), cognitive bias (Palmisano & Chan, 2004) and quantity perception (Seno et al, 2011c) have also been reported, as well as relationships between vection and multiple modalities (e.g. Riecke et al, 2009), personality attributes of observers (Seno et al, 2011d), and aging and development (Haibach et al, 2009;Shirai et al, 2012). Furthermore vection enhanced a type of visual illusion and the semantic meaning could affect vection strength .…”
Section: Introductionmentioning
confidence: 99%